2020
DOI: 10.3390/w12123557
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Temporal and Spatial Changes in Lakes and Climate Change in the Saline-Alkali Concentrated Distribution Area in the Southwest of Songnen Plain, Northeast China, from 1985 to 2015

Abstract: The southwest of Songnen Plain, Northeast China, has an arid climate and is a typical concentrated distribution area of saline-alkali soil. The terrain here is low-lying, with many small, shallow lakes that are vulnerable to climate change. This paper used Landsat satellite remote sensing images of this area from 1985 to 2015 to perform interpretation of lake water bodies, to classify the lakes according to their areas, and to analyze the spatial dynamic characteristics of lakes in different areas. During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The impacts of climate change were also found in the case study of Li [10] in the saline-alkali area of the Songnen Plain, Northeast China, where more than 25% of the lakes and reservoirs disappeared from 1985 to 2015. Using Landsat satellite imagery, the research found that the average temperature of the ~700 remaining lakes has been rising while their annual precipitation and evaporation have been declining.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…The impacts of climate change were also found in the case study of Li [10] in the saline-alkali area of the Songnen Plain, Northeast China, where more than 25% of the lakes and reservoirs disappeared from 1985 to 2015. Using Landsat satellite imagery, the research found that the average temperature of the ~700 remaining lakes has been rising while their annual precipitation and evaporation have been declining.…”
mentioning
confidence: 70%
“…(2) hydropower [3][4][5]; (3) sediment cycling [6]; (4) water storage and supply [7][8][9]; (5) climate change [10]; (6) flood control [5]; (7) fisheries [11] and (8) tourism [12]. Together with a description of these ES, a brief summary of these papers is provided below.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Songnen Plain is the largest distribution area of carbonate saline soil in China and is also one of the three major distribution areas of soda saline-alkali soil in the world [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the coarse spatial resolution and the relatively short-term historical archives of these ocean color sensors, their applications were limited to large lakes and reservoirs, and the study periods were concentrated in the past two decades (Li et al, 2020a). The statistics on lakes with an area ≤ 1 km 2 are scant, and understanding of the variations in SD before the 21st century is limited (Downing et al, 2012;Biggs et al, 2017;Li et al, 2020b). In order to improve the water environment monitoring capability, 30 m Landsat series data have recently been used for SD evaluation (Page et al, 2019;Dona et al, 2014).…”
Section: Introductionmentioning
confidence: 99%